2013
DOI: 10.1002/tea.21132
|View full text |Cite
|
Sign up to set email alerts
|

Death discussion in science read‐alouds: Cognitive, sociolinguistic, and moral processes

Abstract: Little research has been conducted on how to address the complex topic of death when teaching science to children. The present paper addresses this issue by examining how three elementary teachers discuss the death of wild animals during science read‐aloud sessions. Our findings reveal the variety of ways in which nonhuman death can be cognitively, sociolinguistically and morally organized in such contexts. In terms of cognition, animal death was conceptualized metaphorically in terms of linear or cyclic motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…What is interesting in this present study is that the students were not wildlife enthusiasts but still engaged emotionally with the impacts of climate change on other organisms. Oliveira, Reis, Chaize, and Snyder () also found that animals provided a source of engagement in their study of discussions of death in elementary classrooms. Using metaphorical representations of animals' deaths in response to environmental issues provided a means for elementary students and their teachers to engage deeply about death.…”
Section: Discussionmentioning
confidence: 96%
“…What is interesting in this present study is that the students were not wildlife enthusiasts but still engaged emotionally with the impacts of climate change on other organisms. Oliveira, Reis, Chaize, and Snyder () also found that animals provided a source of engagement in their study of discussions of death in elementary classrooms. Using metaphorical representations of animals' deaths in response to environmental issues provided a means for elementary students and their teachers to engage deeply about death.…”
Section: Discussionmentioning
confidence: 96%
“…Chaize, and M.A. Snyder, , Journal of Research in Science Teaching , 51 (2), p. 128. Copyright 2013 by Wiley.…”
Section: A Recent Studymentioning
confidence: 99%
“…Carol uses a motion verb ( to go ) as a scientific metaphor (Filipovic, ), where dying is conceptualized as a type of motion. Death is “a change of location along a biological path” (Oliveira et al., , p. 131). Carol's choice of the word eaten shows movement by transfer of energy from one organism to another.…”
Section: A Recent Studymentioning
confidence: 99%
See 2 more Smart Citations